Pemanfaatan Mobile JKN untuk Pndaftaran Online di Rumah Sakit Jiwa Menur Surabaya - Ibrahim, Mochammad Malik; Eka Yusmanisari; Ria Irmanda Putri Melani; Rizkynieta Dwi Impiani; Wulan Ayu Puspita (Program Studi D3 Rekam Medis dan Informasi Kesehatan, 2025)
In Indonesia itself, there is social health insurance called BPJS. In this research, judging from the large number of participating members, BPJS presents the JKN Mobile Application as a bridge between patients and health facilities to access services. This research aims to successfully utilize the JKN Mobile Application and create access to services that are easy and accessible anywhere. The research conducted at Menur Mental Hospital was reviewed from three behavioral theories, namely Predisposing Factors, which are variables within a person in terms of age, education and knowledge in capturing information, Enabling Factors are supporting factors for both facilities and infrastructure, and reinforcing Factors are Reinforcing Factors. Guarantee security in an action. The research method used is quantitative with a quantitative approach, data collection is carried out by interviews and observations by researchers. The results of this research are that users of the JKN Mobile Application at Jiwa Menur Hospital during August only reached 0.05%, for predisposing factors with insufficient knowledge as much as 47%, Enabling factors with the obstacle of not having a device (cellphone) from the patient to support online registration as well as credit which is not available for registration of the JKN Mobile Application, the Reinforcing or strengthening factor is with support from Menur Mental Hospital Promkes officers who carry out outreach 3 times a week. Keyword: BPJS, JKN Mobile Application, Online Registration